(untitled) (International Journal of World Civilizations and Philosophical Studies, 2024)
Work stress has become a significant issue in dynamic organisations in recent years. According to a literature review examining both civilisation and empirical previous studies, the impact of work stress on family well-being appears inconsistent. This study offers a review and content analysis of qualitative work stress research and promotes terminological clarity in research and practice. The proposed factors serve as a guide and foundation for future research aligning with the conceptual definitions. Consequently, the findings from this review help ensure consistent terminology in work stress research. Previous studies highlight that work stress is characterised by three main dimensions: role ambiguity, role conflict, and role overload. Recent research indicates that employees who effectively manage role ambiguity, role conflict, and role overload can enhance their families’ well-being. Despite the intriguing nature, the significant impact of work stress is often underemphasised in both previous empirical and civilisation-based literature. Therefore, this study comprehensively reviews perspectives, literature, theory, discussion, and conclusions.